Chemical studies and biological activities of extractives from the stems of piper betle - Erny Zuriana, Morshidi (Universiti Malaysia Sarawak (UNIMAS), 2008)
Stems of Piper betle was extracted, isolated, and purified. Hexane partition gave yield 0.44% ethyl acetate partition gave 1.001 %, DCM gave 2.363% and methanol partition gave 2.919%. The toxicity tests for every fraction were done using brine shrimp, termites and bacteria. It is found that the extracts were toxic against termites and bacteria but not active against brine shrimp. The fractions with well-separated spots were subjected to GCIMS to determine its purity and molecular mass. Only semi pure compound obtained and the compound was subjected to FTIR to determine functional group of the compound. The compound is derivative of 1,2-benzenedicarboxylic acid. The bioactive compound from the stem of Piper betle can be applied as an environmental friendly insecticidal in order to replace the pesticide that cause harm to our nature. The compound can also be applied as antibacterial drug.